Struktur dan Profil Vegetasi Habitat Kukang Kalimantan (Nycticebus menagensis) Pelepasliaran Yayasan IAR Indonesia Di Hutan Lindung Gunung Tarak - Indah Winarti, Desi, Riza Linda (Universitas Tanjungpura, 2017)
The vegetation habitat of borneo slow loris in West Kalimantan has quite high potential for damage due to anthropogenic influences. The study aims to find out about the composition, structure and habitat vegetation profile of borneo slow loris at the release area of IAR Indonesia in Tarak Mountain Protection Forest. The data were collected from March to May 2016, by making plot transect. There were two transects consisting of three plots the size of 20 x 20m with four squared plots. The vegetation observed were trees, poles, saplings, seedlings and floor coverings. The data taken were the local and scientific names, number of individuals and habitus. The analysis was conducted on the density, relative density, frequency, relative frequency, dominance, relative dominance, Important Value Index (IVI), Diversity Index (H’) and dominance index (C’). The profile data taken were the position of trees, height of trees, height of first branching, DBH, crown cover, gap and stratification. The results of research showed that the vegetation composition comprised of 23 species of plants. The structure of the vegetation showed the highest IVI of tree regeneration i.e. Syzygium cuminii (117.14%) and the floor covering i.e. Piper crocatum (200%), H’ tree regeneration from 1.47 to 2.55, and floor coverings 0.00, C’ tree regeneration 0. 09 to 0.26 and floor coverings 1.00. The vegetation structure is composed of five strata, there is a vertical gap (± 1 m) and a horizontal gap (>2 m).